Waste materials used in concrete manufacturing - Chandra, Satish, 1943- (Noyes Publications, 1997)
One of the most critical problems we are facing today is acid rain. One of the main causes is the burning of fossil fuels, and as a result, sulfuric acid and carbon dioxide are added to the atmosphere. These gases have detrimental effects on building materials. Thus, there are two problems: (1) to decrease the gas emission, and (2) to produce construction materials more durable to the aggressive pollutant gases and acid rain. The environmental aspects involved in the production and use of cement, concrete and other building materials are of growing importance. Substitution of waste materials will conserve dwindling resources, and will avoid the environmental and ecological damages caused by quarrying and exploitation of the raw materials for making cement. To some extent, it will help to solve the problem otherwise en-countered in disposing of the wastes.
Keywords: Concrete -- Additives.; Waste products.; elektronické knihy; electronic books